Raden Ngabehi Ronggowarsito Teachings-Based REBT Counseling: A Study of Raden Ngabehi Ronggowarsito Teachings in REBT Counseling Perspective (Jurnal Bimbingan Konseling, 2019)
Counseling will be more effective when a counselor understands the cultural background of clients. Therefore, this study aimed to describe the implementation of REBT counseling that is Javanese culture friendly, especially to the adherents of Raden Ngabehi Ronggowarsito’ teachings. The study belonged to qualitative research on discourse analysis. The main source this study was the master piece work by Raden Ngabehi Ronggowarsito, namely: Serat Wirid Hidayat Jati, Serat Kalatidha, Serat Sabda Djati, Serat Sabda Tomo, Serat Joko Lodhang, Serat Jayengbaya, Serat Wedharaga. Raden Ngabehi Ronggowarsito’s teachings always include morals and spirituality in life. Even his teachings became the main character in rationality reasoning, so the rationality is relevant to Javanese culture. The results of this study are expected to be implemented in the practice of REBT counseling with a Javanese culture nuance that is a collaboration between REBT and Raden Ngabehi Ronggowarsito’ teachings. At last, these findings enrich theories in the context of multicultural counseling.